2013
DOI: 10.1200/jco.2012.46.2143
|View full text |Cite
|
Sign up to set email alerts
|

Cytokine Genetic Variations and Fatigue Among Patients With Breast Cancer

Abstract: Purpose Fatigue is a common adverse effect of cancer treatment and may persist for years after treatment completion. However, risk factors for post-treatment fatigue have not been determined. On the basis of studies suggesting an inflammatory basis for fatigue, this study tested the hypothesis that expression-regulating polymorphisms in proinflammatory cytokine genes would predict post-treatment fatigue in breast cancer survivors. Patients and Methods Women diagnosed with early-stage breast cancer (n = 171) co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
108
4
4

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 113 publications
(119 citation statements)
references
References 54 publications
(9 reference statements)
3
108
4
4
Order By: Relevance
“…CRF and cachexia are both associated with elevated inflammatory cytokines. [17][18][19][20] In addition, cachexia has been noted to cause myocardial dysfunction in animal models. [21] High levels of inflammatory cytokines are associated with a poor prognosis in cancer patients and with worsening cardiac disease including systolic dysfunction in more general cohorts.…”
Section: Strain As a Nonspecific Marker Of Prognosis In Cancer Patientsmentioning
confidence: 99%
“…CRF and cachexia are both associated with elevated inflammatory cytokines. [17][18][19][20] In addition, cachexia has been noted to cause myocardial dysfunction in animal models. [21] High levels of inflammatory cytokines are associated with a poor prognosis in cancer patients and with worsening cardiac disease including systolic dysfunction in more general cohorts.…”
Section: Strain As a Nonspecific Marker Of Prognosis In Cancer Patientsmentioning
confidence: 99%
“…Their results demonstrated that fatigue was significantly associated with both TNF-308 and IL6-174 but was not associated with IL1B-511 C>T. The addition of TNF-308 previously established to be associated with fatigue among oncology patients undergoing treatment [62] might have enhanced the sensitivity of Bower et al study to detect SNPs association with fatigue. Although this recent study [61] suggests that breast cancer patients harbouring certain variants of cytokines genes may be at higher risk of developing fatigue, it still cannot be concluded at this point if genetic variants of pro-inflammatory cytokines could serve as clinical genetic biomarkers to predict breast cancer patients who have higher risk of having fatigue. Indeed, more studies involving additional genetic variants especially in a larger cohort of different ethnicities are needed.…”
Section: Cytokine Genes and Fatigue And Energymentioning
confidence: 94%
“…The roles of pro-inflammatory cytokines genetic polymorphisms in developing breast cancer-associated depression was further provided by Bower et al who established that breast cancer patients with heterozygous GG genotype of IL6-174 SNP experienced higher depressive symptoms when compared with those carrying the GC and CC genotypes [61]. Another similar study [75] reported that breast cancer patients who were homozygous for a rare allele variant of TNF-α (rs1799964) had lower odds of developing subsyndromal depression.…”
Section: Psychological Distressmentioning
confidence: 96%
See 2 more Smart Citations